2015
DOI: 10.1257/aer.20130935
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Scrappage and Gasoline Policy

Abstract: We estimate the sensitivity of scrap decisions to changes in used car values -the "scrap elasticity" -and show how it influences used car fleets under policies aimed at reducing gasoline use. Large scrap elasticities produce emissions leakage under efficiency standards as the longevity of used vehicles is increased, a process known as the Gruenspecht effect. To explore the magnitude of this leakage we assemble a novel dataset of U.S. used vehicle registrations and prices, which we relate through time via diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Increases in the fuel economy of initial kept vehicles due to an increased standard will increased demand for used fuel‐inefficient vehicles. The increase in demand will lead used gas guzzlers to be more valuable, and thus more slowly retire from the fleet (similar to the effect documented in Jacobsen and van Benthem (2015)). Furthermore, it cannot realistically be argued that fuel economy of the bought vehicle will be constrained by the standards themselves.…”
Section: Policy Implicationsmentioning
confidence: 59%
“…Increases in the fuel economy of initial kept vehicles due to an increased standard will increased demand for used fuel‐inefficient vehicles. The increase in demand will lead used gas guzzlers to be more valuable, and thus more slowly retire from the fleet (similar to the effect documented in Jacobsen and van Benthem (2015)). Furthermore, it cannot realistically be argued that fuel economy of the bought vehicle will be constrained by the standards themselves.…”
Section: Policy Implicationsmentioning
confidence: 59%
“…The first segment evaluates the welfare implications of CAFE from a microeconomic perspective (Austin & Dinan, ; Jacobsen, ; Kleit, ; Klier & Linn, ; Leard et al., ; Liu et al., ). Related studies have examined the effects of CAFE on costs of production, new vehicle prices, vehicle sales, used vehicle prices, vehicle scrappage rates, fleet fuel economy, and vehicle safety (see, e.g., Anderson & Sallee, ; Austin & Dinan, ; Bento et al., ; Clerides & Zachariadis, ; Goldberg, ; Greene, ; Jacobsen, ; Jacobsen & van Benthem, ; Klier & Lin, ; McAlinden et al., ). In addition, several authors have compared the welfare effects of CAFE with those of an alternative price instrument (i.e., a higher gasoline tax or carbon tax), and found that the latter is more cost effective (e.g., see Austin & Dinan, ; Davis & Knittel, ; Goldberg, ; Karplus et al., ; Kleit, ).…”
Section: Us Federal Mileage and Carbon Dioxide Standardsmentioning
confidence: 99%
“…These studies have generally concluded that both new vehicle purchases and used vehicle scrappage respond to gasoline prices (Li, Timmins, von Haefen 2009, Klier and Linn 2012, Knittel 2012, and Jacobsen and van Benthem 2013. At the intensive margin, households reduce driving where gasoline price rises (Small andvan Dender 2007, Gillingham 2013).…”
Section: Fleet Fuel Economy Of Us Public Transit Bus Is Energy Pricmentioning
confidence: 99%